Conventional Ultrasonography: A Remarkable Tool in Early Detection of Benign Ovarian Lesions in Comparison to Gold Standard MRI - Jabeen, Naila; Walid, Ayesha; Rasheed, Binish; Naz, Nasreen; Rahim, Anila; Siddiqui, Rabeeya Qutub uddin (Pakistan Armed Forces Medical Journal, 2023)
Objective: This study aimed to assess the efficiency of ultrasonography in the accurate diagnosis of benign ovarian lesions as compared to the gold standard Magnetic Resonance Imaging (MRI). Study Design: Prospective analytical cross-sectional study. Place and Duration of Study: Dow Institute of Radiology, Dow University of health sciences (DUHS), OJHA Campus, Karachi, Pakistan, from Jun 2018 to Nov 2019 Methodology: The consecutive sampling technique was used to recruit the patients. The frequency and percentage, and mean and standard deviation were calculated for qualitative and quantitative variables, respectively. The p-value <0.05 considered as significant. Results: Majority of the patients were aged ≥20 years (49.06%) and were obese (13.21%). Majority of the participants (88.68%) were married where 69.81% had normal menstrual status and 11.32% had menopause. On cross-tabulation, tumor status (Benign) was found to have a very high significant association with age and BMI at p-value <0.001 and menstrual status at pvalue 0.000. Benign lesions were most prevalent (60.47%) among 20-29 years old and the PPV is 92.86%; Diagnostic accuracy for this age group is 95.35%. PPV, NPV, sensitivity, specificity, and diagnostic accuracy were 100 % for Underweight, premenopause patients with 16 to 30 days symptoms. Benign tumor was more prevalent among patients with normal BMI (93.48%), post-menopause (63.64%), symptoms’ duration of 1 to 3years (66.67%), single (37.06%) and cystic mass (49.52%). Conclusion: Ultrasonography showed excellent diagnostic accuracy in the detection of benign ovarian tumors.